Achievement motivation, retirement decision and concept of generativity among government employees of Victorias City - Crisosto, Manilyn Charisse G.; Salido, Mary Lou B. (2009.)
The study sought to identify the achievement motivation, factors affecting retirement decision, and concept of generativity of government employees. It shows that government employees have high achievement motivation and tend to be successful in competition, cooperative, rational and successful in their careers. They considered financial situation, health status, family's condition, number of dependents and spending leisure time with family as important factors in retirement decision.
Thesis (Undergarduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Retirement decision of government employees